Male Factor Infertility and Clomiphene Citrate: A Meta‐Analysis—The Effect of Clomiphene Citrate on Oligospermia. Issue 4 (July 2015) - Bridges, Naima; Trofimenko, Vera; Fields, Sally; Carrell, Douglas; Aston, Kenneth; Hotaling, James
Abstract : Introduction: : Clomiphene citrate has long been administered with inconclusive outcomes. It has often been used as empirical treatment for male factor infertility, presumably by increasing the sperm concentration. However, to our knowledge there has been no meta‐analysis of the exact impact on semen parameters. We performed a systematic review and meta‐analysis of the impact of clomiphene citrate on sperm parameters in men with oligospermia. Methods: : We systematically reviewed pertinent randomized, controlled, prospective trials using the bibliographic databases MEDLINE® (1966 to 2013), Embase® (1980 to 2013) and the Cochrane Collaboration. References of selected articles were reviewed for additional relevant citations. The net treatment effect of the observed change in sperm concentration was analyzed. Results: : Data pooled from 2 randomized, controlled trials and 1 prospective trial in men with infertility and oligospermia included a total of 197 men with a mean age of 32.8 years (range 18 to 65). In the treatment arm 115 men were treated with a minimum dose of 25 mg clomiphene citrate at least every other day for a minimum of 3 months. The placebo or no treatment arm included 82 men. Pooled meta‐analysis data revealed a highly significant increase of 7.7 million sperm per ml after administering clomiphene citrate compared to placebo or no treatment. There was no evidence of significant heterogeneity across the groups. Conclusions: : Available data suggest that clomiphene citrate is associated with an increased sperm count compared to placebo.